Mengukur Pencapaian Sustainable Development Goals 2030 Melalui Pembangunan Bandara Yogyakarta International Airport - Fiya Ainur Rohmatika; Hidayat Chusnul Chotimah; Erti Kusuma Siahaan; Yenis Contesa (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (JEBMA), 2022)
The YIA airport was built as part of a national master plan to open up economic channels, including export and import, and internationalise the Yogyakarta region. The building of this airport generates an anomaly that is in conflict with the state of the community and the affected environment surrounding the airport, particularly in terms of meeting the SDGs by 2030. Researchers believe that the spectacular infrastructure's state in achieving economic growth is insufficient since the community's environmental and social characteristics also affect the success of the SDG's in regional development, including the development of the airport industry. This study employs qualitative research methodologies to describe the answers to the formulation of the problems investigated through online and offline interviews with the DIY PUP-ESDM Office, Bappeda Kulon Progo, and the people of Palihan Village, Temon District. The findings indicate that efforts to accomplish sustainable development goals from the economic, social, and environmental pillars can be directly tied to the construction of YIA airport. In this regard, synergy and effective communication between the government, those responsible for implementing airport operations, and the local population in Kulon Progo are crucial.